PEMBERDAYAAN MASYARAKAT DALAM PENGGOLONGAN OBAT DAN JAMU DI KABUPATEN KLATEN - Sunarmi; Subarti, Dwi; Suhendriyo (CV SWA Anugerah, 2025)
Medicine and herbal medicine have become one of the needs for the community, especially when we are sick. Not infrequently, when we are sick we are reluctant to see a doctor but instead go to a shop or pharmacy to buy medicine. Based on the general guidelines of the Indonesian National Drug Laboratory, it states that according to applicable provisions, before being approved for distribution in Indonesia, Medicine and Herbal Medicine must go through an assessment of efficacy, safety, and quality. One of the information that must be known by the community is regarding the classification of medicines and herbal medicines. Community Service activities carried out in the form of health education for PKK mothers in Dk. Kergan, Bakung Village, Jogonalan, Klaten. The forms of activities carried out were lectures, simulations, demonstrations and discussions using media in the form of power point slides, videos and examples of medicines and herbal medicines that are commonly consumed in households. The results of these activities have provided additional information for the community regarding the use of safe and efficacious medicines and herbal medicines. With this community service program, it is hoped that it can increase public awareness in the proper use of medicines and herbal medicines.